2009
DOI: 10.1007/s11104-009-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and element concentrations of Norway spruce needle litter with differing B, N, or P status

Abstract: Adequate boron (B) nutrition may decrease concentrations of phenolic compounds and enhance structural integrity and lignification in plants, compared with suboptimal B. This could affect decomposition in areas where B deficiencies are common. The mass loss and changes in element concentrations in Norway spruce needle litter were studied with combinations of litter from high-B and low-B trees, incubated for 29 months, in either B fertilised or control plots without B addition. The litter originated from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The mass losses of the needles in the present study were comparable to those reported for Norway spruce and Scots pine needles in earlier studies on mineral soil sites (Lundmark-Thelin and Johansson, 1997;Hyvönen et al, 2000;Palviainen et al, 2004b;Lehto et al, 2010). No significant differences in the mass loss, nutrient or metal dynamics of the harvest residue needles were found between the clear-cut and control sites.…”
Section: Impacts Of Clear-cutting and Study Locationsupporting
confidence: 86%
See 3 more Smart Citations
“…The mass losses of the needles in the present study were comparable to those reported for Norway spruce and Scots pine needles in earlier studies on mineral soil sites (Lundmark-Thelin and Johansson, 1997;Hyvönen et al, 2000;Palviainen et al, 2004b;Lehto et al, 2010). No significant differences in the mass loss, nutrient or metal dynamics of the harvest residue needles were found between the clear-cut and control sites.…”
Section: Impacts Of Clear-cutting and Study Locationsupporting
confidence: 86%
“…The net accumulation in the spruce needles was approximately 333 % after 3 years, and the net release from the pine needles was approximately 19%. On mineral soils accumulation of Al into Norway spruce needles (Lehto et al, 2010) and some other conifer litter types (Rustad and Cronan, 1988;Rustad, 1994) has been confirmed earlier. The release of Al from pine needles is consistent with a study by Palviainen et al (2004a), where the net release from pine harvest residue needles over 3 years was approximately 26%.…”
Section: Impact Of Tree Speciesmentioning
confidence: 55%
See 2 more Smart Citations
“…Boron level during growth slightly increased the initial mass loss in silver birch leaf litter (Lehto et al, 2010a), however, Norway spruce litter was not affected (Lehto et al, 2010b). Lignin concentrations in Norway spruce needle litter were decreased as a result of B fertilisation, but only if P was also applied.…”
Section: Wood Quality Litter Quality and Decompositionmentioning
confidence: 89%